The Effect of Doxycycline on Matrix Metalloproteinase-9 Levels in the Colon of Wistar Rats with Obstructive Ileus - Ulfandi, Devby; Labeda, Ibrahim; Syarifuddin, Erwin; Zainuddin, Andi Alfian; Faruk, Muhammad (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: Obstructive ileus after colonic anastomosis resection can increase leakage up to 2.5-fold. One possibility could be the extracellular matrix degradation, where matrix metalloproteinase-9 (MMP-9) negatively influences anastomotic healing. This study aimed to determine the effect of doxycycline on MMP-9 levels in the colon of experimental rats with obstructive ileus. MATERIALS AND METHODS: In this study, 28 male Wistar rats were selected randomly in a post-test control-group design comprising: Group A - control group, Group B - group without obstructive ileus given doxycycline, Group C - group with obstructive ileus not given doxycycline, and Group D - group with obstructive ileus given doxycycline. Doxycycline was given at a dose of 30 mg/kg. Groups C and D underwent anastomotic resection 24 hours following obstructive ileus procedure. Groups A and B underwent anastomotic resection at the same time as Groups C and D. Colonic tissue was collected to examine MMP-9 levels using an enzyme-linked immunosorbent assay (ELISA). Data were compared using Shapiro–Wilk tests, ANOVA, and Mann–Whitney U tests, and p<0.05 was considered significant. RESULTS: The results showed that the average MMP-9 levels increased with doxycycline treatment, [Group C (4.294 ± 0.226)], with significantly higher MMP-9 levels than Group A (1.017 ± 1.569, p<0.001). Group B did not differ significantly from Group A (p=0.848). MMP-9 levels differed significantly between Groups B and D (p<0.001), and between Groups C and D (p<0.001). CONCLUSION: Oral administration of doxycycline can attenuate increasing MMP-9 levels in Wistar rats with obstructive ileus